Analisis Strategi Marketing Mix dalam Meningkatkan Pendapatan pada Toko Buah Daisuki Fruits, Sarilamak dalam Perspektif Bisnis Syariah - Pratiwi Rahmadani; Iiz Izmuddin (Lembaga Yasin AlSys, 2026)
Although the marketing mix strategy has been widely examined in marketing research, studies specifically addressing its implementation in increasing the revenue of fruit retail businesses from an Islamic business perspective remain limited. This study aimed to analyse the implementation of the marketing mix strategy in increasing the revenue of Daisuki Fruits Sarilamak Store from an Islamic business perspective. This study employed a qualitative approach with a case study design. The research informants consisted of the business owner, employees, and consumers selected using purposive sampling. Data were collected through observations, in-depth interviews, and documentation and were subsequently analysed using the interactive model of Miles, Huberman, and Saldaña, which comprises data condensation, data presentation, and conclusion drawing and verification. The results showed that the marketing mix strategy, comprising product, price, place, and promotion, contributed positively to increasing business revenue. The product strategy was implemented by providing high-quality and diverse fruits, whereas the pricing strategy was implemented competitively and transparently. The place strategy was supported by convenient distribution and ordering services, while the promotion strategy was implemented through social media and word-of-mouth communication, although the use of digital marketing still needs to be optimized. The SWOT analysis showed that the W–O strategy was the priority for business development through the utilization of external opportunities to overcome internal weaknesses. These findings confirm that the implementation of a marketing mix aligned with Islamic business principles can support increased revenue and business competitiveness. This study provides a theoretical contribution to the development of Islamic marketing studies and practical implications for micro, small, and medium enterprises in formulating effective, competitive, and sustainable marketing strategies.